Modification Of PVDF Membrane Using Lignin And Calcium Carbonate For Oily Water Separation To Be Used In Water Dispenser - Rajesveran, Dinesvaran (Universiti Sains Malaysia, 2021)
Lignin is the world's second most abundant biopolymer and source of aromatic structures which consist of plenty of hydrophilic groups. Lignin have the ability to be used as a hydrophilic promoter in membrane fabrication due to its property which able to improve the hydrophilicity and antifouling properties of hydrophobic membranes. In this work, lignin was introduced and coated on both polyvinylidene fluoride, PVDF and PVDF with CaCO3 loading for oily water separation. PVDF and PVDF with 3 wt% CaCO3 loading membranes were immersed in 0.75 g of the lignin solution containing sodium chloride, NaOH and distilled water. The pristine PVDF and lignin coated membranes were characterized with Fourier-transform infrared (FTIR) spectroscopy, and scanning electron microscope (SEM) for comparison. The dynamic underwater contact angle was used to examine the hydrophilic properties of the modifed membranes. The pure water permeability was greatest in PVDF_lignin_CaCO3 removal (PVDF-Lig-CCR), followed by PVDF_lignin_CaCO3(PVDF-Lig-CC), pristine PVDF and PVDF_lignin (PVDF-Lig). The usage of 0.2 M EDTA-disodium solution able to remove the calcium carbonate as the porosity of the modified membrane is reduced. The PVDF-coated lignin membrane exhibits antifouling properties with oil rejection up to 99.36% while the pristine PVDF membrane only rejected 87.50%. The presence of lignin as a hydrophilic promoter coated on PVDF membrane showed a good antifouling performance although it has lower but stable oily water permeability.